The Evolution of Rice Production Practices - Eulito U. Bautista; Evelyn F. Javier (Philippine Institute for Development Studies (PIDS), 2005)
This paper presents a summary of the evolution of major practices in rice production over the last 100 years in the country. These practices essentially evolved out of the changes in the varieties introduced and planted by Filipino farmers, which have to change the manner by which production and postharvest operations have to be done in order to maximize productivity and reduce costs. Varieties were introduced in three major periods: the pre-Green Revolution era dominated mainly by traditional varieties which were planted once a year, the Green Revolution period of 1966 to 1988 which was characterized by the diffusion of modern high-yielding varieties which are planted for two seasons per year, and the post-Green Revolution period from 1989 to the present times. As varieties changed over time, farmers practices also changed to attain maximum yield potential of the varieties as well as in response to goals of higher productivity, greater efficiency, and, for the present period, environmental sustainability.
Keywords: 330; mechanization; paddy; rice production; farmers' practices; traditional varieties; Green Revolution technologies; modern varieties; direct seeding; integrated nutrient and pest management; postharvest; Reisanbau; Agrarproduktion; Reispolitik; Technischer Fortschritt; Philippinen